2012
DOI: 10.1128/iai.00635-12
|View full text |Cite
|
Sign up to set email alerts
|

Capsular Polysaccharide of Erysipelothrix rhusiopathiae, the Causative Agent of Swine Erysipelas, and Its Modification with Phosphorylcholine

Abstract: The capsule has been implicated in the virulence of the swine pathogen Erysipelothrix rhusiopathiae, a rod-shaped, intracellular Gram-positive bacterium that has a unique phylogenetic position in the phylum Firmicutes and is a close relative of Mollicutes (mycoplasma species). In this study, we analyzed the genetic locus and composition of the capsular polysaccharide (CPS) of the Fujisawa strain of E. rhusiopathiae. Genome analysis of the Fujisawa strain revealed that the genetic locus for capsular polysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 35 publications
0
32
1
Order By: Relevance
“…Several polysaccharide modifications can be found in the structures that aid in this role, including sialyl groups and phosphorylcholine (25,(76)(77)(78). The presence of sialyl groups in the newly published structures may be an important factor for virulence of this bacterium, as has been suggested for H. parasuis and shown in H. influenzae (25,76,77).…”
Section: Resultsmentioning
confidence: 98%
“…Several polysaccharide modifications can be found in the structures that aid in this role, including sialyl groups and phosphorylcholine (25,(76)(77)(78). The presence of sialyl groups in the newly published structures may be an important factor for virulence of this bacterium, as has been suggested for H. parasuis and shown in H. influenzae (25,76,77).…”
Section: Resultsmentioning
confidence: 98%
“…It has been hypothesized that this ability to persist in the environment for extended periods, in addition to E. rhusiopathiae 's wide host range, are the most important factors facilitating its widespread distribution (Brooke and Riley, 1999). Several virulence factors have been demonstrated or suggested for this bacterium, including neuraminidase, surface protective antigen A and the capsular polysaccharide (Ogawa et al, 2011; Shi et al, 2012), the majority of which appear to be commonly present (Janßen et al, 2015). Isolates of E. rhusiopathiae sequenced to date fall into three distinct clades, all of which appear to have retained some degree of host generalism (Forde et al, 2016), suggesting that most strains can likely be transmitted between species.…”
Section: Introductionmentioning
confidence: 99%
“…E. rhusio-pathiae lacks many orthologous genes for the biosynthesis of wall teichoic acids (WTA) and LTA, as well as the dltABCD operon, which is responsible for the incorporation of D-alanine into WTA and LTA (2). Furthermore, recent analysis of the capsular polysaccharide of E. rhusiopathiae indicated that this bacterium indeed has a complex, heterogeneous capsule that is modified by phosphocholine (22). The same study also suggested that there could be some overlap between the biosynthesis pathways of capsular polysaccharides and other cell wall components, including WTA and/or LTA (22).…”
mentioning
confidence: 99%
“…Furthermore, recent analysis of the capsular polysaccharide of E. rhusiopathiae indicated that this bacterium indeed has a complex, heterogeneous capsule that is modified by phosphocholine (22). The same study also suggested that there could be some overlap between the biosynthesis pathways of capsular polysaccharides and other cell wall components, including WTA and/or LTA (22). Thus, in addition to its unique phylogenetic position as a member of the Firmicutes, it appears that the cell wall structure of E. rhusiopathiae may also be unique among Grampositive bacteria.…”
mentioning
confidence: 99%